Solution-Processed Pure Blue Thermally Activated Delayed Fluorescence Emitter Organic Light-Emitting Diodes With Narrowband Emission - Xu, Ting; Liang, Xiao; Xie, Guohua (Frontiers in Chemistry, 2021)
There is a need to satisfy the high color purity requirement of display technology with a simply fabricated process. Herein, solution-processed blue thermally activated delayed fluorescence organic light-emitting diodes (OLEDs) with a narrow spectrum with a full width at half maximum (FWHM) of 32 nm and y color coordinate below 0.2 are demonstrated by employing a molecule containing boron and nitrogen atoms (TBN-TPA) as the guest emitter in the emissive layer. The opposite resonance positions of B-N atoms of TBN-TPA endows a multi-resonance effect, leading to high color purity.